2013
DOI: 10.1097/sih.0b013e31827437e5
|View full text |Cite
|
Sign up to set email alerts
|

Are Medical Students Being Taught Invasive Skills Using Simulation?

Abstract: Although most medical students receive formal instruction in basic procedures, fewer receive formal instruction in advanced procedures. The use of simulation to complement this training occurs less often. Simulation training should be increased in undergraduate medical education and integrated into graduate medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Several studies indicate that medical students typically do not receive standardized hands-on training on advanced procedural skills 17 19 (our target population is no exception). Among these are intubation, arterial line placement, central line insertion, and lumbar puncture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that medical students typically do not receive standardized hands-on training on advanced procedural skills 17 19 (our target population is no exception). Among these are intubation, arterial line placement, central line insertion, and lumbar puncture.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are intubation, arterial line placement, central line insertion, and lumbar puncture. 17 These are advanced and somewhat invasive procedures that can cause discomfort and/or complications for patients. In this study, we chose to provide second and third year medical students with a student-centered, simulation-based training on these advanced procedures.…”
Section: Introductionmentioning
confidence: 99%
“…One recommended that 'we should also be looking at training in the virtual environment to limit the impact on clinical services in the early year(s),' whilst other comments included forging links with medical education or radiology academies to develop simulation and interprofessional learning. Various methods of simulated learning have been used in health care education [26][27][28][29] and the use of simulator training within ultrasound education, prior to students entering clinical placements, has been evaluated in different settings. 7,30 Simulation has also been suggested as a potential method of ensuring standardised clinical competency assessment, along with other methods of assessing competency.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation skills were innovative educative approaches, which are being increasingly used to train undergraduate and postgraduate health care professionals [18,19]. Several studies have demonstrated the gain in knowledge acquisition, technical gesture acquisition and performance of the trainees in different domains of health care [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%